Analisis Sebaran Data Curah Hujan di Provinsi DKI Jakarta sebagai Proses Quality Control Data Secara Spasial - Pramono, Setyo Aji; Halida, Mutiara (Buletin GAW Bariri (BGB), 2025)
Rainfall plays an important role in the global water and energy cycle. Accurate rainfall predictions are very important to be used as a warning for hydrometeorological disasters. Therefore, it is necessary to calculate the relationship (correlation) of rainfall between regions to see the extent to which rainfall in one place affects rainfall in another place. It is also necessary to see the difference in rainfall values ​​between these regions to be used as a reference that this difference in value is the minimum acceptable value. The Spatial Quality Control (QC) method is used to see the difference in rainfall values ​​between locations. This method uses the calculation of rainfall data correlation, then an analysis is carried out from the results of the correlation value and associated with the distance between the locations. The results obtained are that the distance considered ideal in the rainfall phenomenon in Jakarta Province is 7.9 km with a correlation value above 0.71, while the average rainfall value that is still considered good is below 10 mm / day.